A Mediterranean Sea Wave Spectral Model - Lazanoff, Sheldon M; Stevenson, Norman M; Cardone, Vincent J (1973)
An operational Mediterranean wave spectral model has been developed through the cooperative efforts of the U.S. Naval Oceanographic Office (NAVOCEANO), Fleet Numerical Weather Central (FNWC) and New York University (NYU). Since April 1972, the model has been operating in a real-time environment (analyses/prognosis to 48 hours). The model is a modified version of the original NYU North Atlantic wave model and has two main parts: (1) wave energy growth based on a modified version of the Miles-Phillips growth mechanism and dissipation at individual grid points and (2) wave energy propagation from grid point to grid point. The Mediterranean wave model uses a conic conformal grid, permitting the assumption of equal spacing between grid points. There are 455 sea points with a mesh length of 67 km. The wave model driving force is a modified version of the FNWC Marine Wind model which has a mesh length of approximately 370 kms. For use in the Mediterranean, the winds are interpolated between Marine Wind field grid points. At analysis/pre-analysis times, wind reports from synoptic ship files are reanalyzed in the Mediterranean wind program so that local wind phenomena, such as 'mistrals,' are included in the wind field.